Effect of tricarboxylic acid cycle regulator on carbon retention and organic component transformation during food waste composting. (May 2018) - Lu, Qian; Zhao, Yue; Gao, Xintong; Wu, Junqiu; Zhou, Haixuan; Tang, Pengfei; Wei, Qingbin; Wei, Zimin
Graphical abstract: Highlights: Malonic acid can be reducing the greenhouse gas emission during composting. Assess the degradation and transformation of organic component during composting. Compare the diversity of bacterial and fungal community in different treatment. Extra energy supply strengthened the degradation of organic component by bacteria. Mechanism of organic component transformation with TCA cycle regulator is proposed. Abstract: Composting is an environment friendly method to recycling organic waste. However, with the increasing concern about greenhouse gases generated in global atmosphere, it is significant to reduce the emission of carbon dioxide (CO2 ). This study analyzes tricarboxylic acid (TCA) cycle regulators on the effect of reducing CO2 emission, and the relationship among organic component (OC) degradation and transformation and microorganism during composting. The results showed that adding adenosine tri-phosphate (ATP) and nicotinamide adenine dinucleotide (NADH) could enhance the transformation of OC and increase the diversity of microorganism community. Malonic acid (MA) as a competitive inhibitor could decrease the emission of CO2 by inhibiting the TCA cycle. A structural equation model was established to explore effects of different OC and microorganism on humic acid (HA) concentration during composting. Furthermore, added MA provided an environmental benefit in reducing the greenhouse gas emission for manufacture sustainable products.